2020
DOI: 10.1101/2020.03.16.20036962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the quality of clinical and administrative data extracted from hospitals: The General Medicine Inpatient Initiative (GEMINI) experience

Abstract: Objective: Large clinical databases are increasingly being used for research and quality improvement, but there remains uncertainty about how computational and manual approaches can be used together to assess and improve the quality of extracted data. The General Medicine Inpatient Initiative (GEMINI) database extracts and standardizes a broad range of data from clinical and administrative hospital data systems, including information about attending physicians, room transfers, laboratory tests, diagnostic imag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…GEMINI data go through a statistical and manual screening process that includes range checks and missing data checks during collection and harmonization. 9 This process is iterative, and data are re-extracted when problems are identified. No additional data-cleaning steps were taken in the preparation of the data for this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GEMINI data go through a statistical and manual screening process that includes range checks and missing data checks during collection and harmonization. 9 This process is iterative, and data are re-extracted when problems are identified. No additional data-cleaning steps were taken in the preparation of the data for this study.…”
Section: Resultsmentioning
confidence: 99%
“…All data were linked using unique identifiers and a subset of the data demonstrated 98%-100% accuracy compared with chart review. 9 We identified all patients who were admitted from LTC facilities using the institution number developed by the Ministry of Health and Long-Term Care Master Numbering System in our administrative data. 10 These facilities included nursing homes and facilities offering complex continuing care but not rehabilitation hospitals.…”
Section: Gemini Data Sources Methods and Variablesmentioning
confidence: 99%
“…Patient‐level data were collected from electronic and administrative sources at each participating hospital, as described previously 5 . GEMINI data have been rigorously validated against manual review of medical records and found to be highly reliable 6 . Patient demographics, diagnoses, and discharge disposition were collected from hospital administrative sources, as reported to the Canadian Institute for Health Information.…”
Section: Methodsmentioning
confidence: 99%
“…Unique identifiers were used to link all data, and analyses on a subset of data showed 98%-100% accuracy compared with chart review. 12 Patients with diabetes were identified using CIHI Diagnosis Code (Group 10, Field 02) which conveys International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10) codes as recorded in hospital administrative databases.…”
Section: Data Sources and Collectionmentioning
confidence: 99%